2017
DOI: 10.21577/0103-5053.20170239
|View full text |Cite
|
Sign up to set email alerts
|

Ditryptophan Cross-Links as Novel Products of Protein Oxidation

Abstract: Protein oxidation is an unavoidable consequence of aerobic metabolism. The oxidation of most proteins residues is non-repairable and may affect protein structure and function. In particular, protein cross-links arising from oxidative modifications are presumably toxic to cells because they may accumulate and induce protein aggregation. However, most of these irreversible protein cross-links remain partially characterized. Up to very recently, ditryptophan cross-links (Trp-Trp), in particular, have been largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 61 publications
(141 reference statements)
0
15
0
1
Order By: Relevance
“…It was shown that the hydroxylation of tryptophan by Fenton's reaction and photolysis oxidation occurs in different positions of the molecule yielding many possible isomers of hydroxytryptophans and monohydroxytryptophan dimers. 21,22 However, none of these studies have ever reported the formation of nanoparticles 21,22 . It is well known that sonication of an aqueous solution results in the formation of H and OH radicals due to acoustic cavitation 15 .…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the hydroxylation of tryptophan by Fenton's reaction and photolysis oxidation occurs in different positions of the molecule yielding many possible isomers of hydroxytryptophans and monohydroxytryptophan dimers. 21,22 However, none of these studies have ever reported the formation of nanoparticles 21,22 . It is well known that sonication of an aqueous solution results in the formation of H and OH radicals due to acoustic cavitation 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the ditryptophan dimer in superoxide dismutase or lysozyme can cleave under MS/MS conditions [ 47 ], suggesting that it is not as stable as a dityrosine link and thus is similar to the labile crosslinks we have detected in the current study. Paviani et al have suggested that the susceptibility to cleavage of ditryptophan is more consistent with a C–N bond than a C–C bond [ 47 ]. Accordingly, the crosslink that is reversed by ascorbate in the current study is likely a C–N bond.…”
Section: Discussionmentioning
confidence: 67%
“…The nature of ditryptophan bonds is not yet fully elucidated [ 47 ]. Available data suggest that C and N participate in ditryptophan crosslinking [ 47 ], giving the possibility of either C–C or C–N crosslinks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations